PENGARUH MANAJEMEN MODAL KERJA DAN STRUKTUR MODAL TERHADAP KINERJA KEUANGAN - Aldo Hartawan; Siti Ruhana Dara (LPMP Imperium, 2019)
This research aims to analyze the effect of receivable turnover, working capital turnover, inventory turnover and debt-equity ratio on financial performance subsector food and beverage companies listed in the Indonesia Stock Exchange period 2014-2018. The research method is a multiple linear regression analysis and analysis method with panel data. The sample is taken by using purposive sampling method, there are 17 companies that meet the criteria. In measuring the working capital management as an independent variable, financial ratios are frequently used receivable turnover, working capital turnover, and inventory turnover. Capital structure frequently used the debt-equity ratio. In measuring financial performance, financial ratios are frequently used to return on equity. the result of the analysis indicates that working capital turnover has a significant effect the financial performance. Receivable turnover, inventory turnover, and the debt-equity ratio has no significant effect on financial performance. And simultaneously overall receivable turnover, working capital turnover, inventory turnover, and debt-equity ratio have a significant effect on financial performance.